Respuesta :

Answer:

78

Step-by-step explanation:

= 12 x^2 - 30         put in ' - 3 ' for  'x'

= 12 ( -3 )^2 - 30

 = 12 (9) - 30 = 78

Answer:

78

Step-by-step explanation:

Expression:

  • 6(2x² - 5)

Evaluate x = 3 according to the question:

[tex]6 \{2 (- 3) {}^{2} - 5) \}[/tex]

Solve this problem, applying PEMDAS.

  • [tex]6 \{2( - 3 \times - 3) - 5 \}[/tex]
  • [tex]6 \{2(9) - 5 \}[/tex]
  • [tex]6 \{18 - 5 \}[/tex]
  • [tex]6 \{13 \}[/tex]
  • [tex]78[/tex]

Hence,the answer to the given expression is 78.

-Regards,Hannah :)